EFEKTIVITAS MAGGOT (HERMETIA ILLUCENS) SEBAGAI PAKAN LELE DENGAN METODE BUDIKDAMBER - Kurniawan, Aditya Teguh; Agustin; Agustin, Heny (Politeknik Pertanian Bogor, 2025)
The high nutritional value of maggots (Hermetia illucens) makes them a potential alternative feed for catfish through the practice of fish farming in buckets (Budikdamber). This research was conducted from September to March 2023 at the Agroecotechnology Experimental Garden, Trilogi University, Jakarta. The study consisted of two experimental sets, each using a one-factor Randomized Complete Block Design (RCBD). The first experiment aimed to determine the most effective growth medium for maggots, consisting of four treatments: rice residue (L1), vegetable waste (L2), coconut pulp (L3), and a combination of rice residue, vegetable waste, and coconut pulp (L4). The results of this first experiment were used to establish the maggot cultivation procedure for the second experiment.The second experiment was designed to evaluate the effectiveness of maggots as feed in catfish and pakcoy cultivation using the Budikdamber system. This experiment involved three feed treatments: commercial pellets (P0), maggots (P1), and a combination of pellets and maggots in a 50:50 ratio (P2), across three planting periods (T) of pakcoy. The results showed that the combination of rice residue, vegetable waste, and coconut pulp was the most effective growth medium for the maggot fattening stage. Feeding catfish with maggots at both 50% and 100% proportions had no significant effect on the harvested length or weight of the fish, nor on the yield of pakcoy cultivated concurrently using the Budikdamber method. These findings indicate that maggots can serve as a viable alternative to commercial pellets in catfish farming.